PENGARUH PEMASARAN ONLINE TERHADAP KEPUTUSAN PEMBELIAN PRODUK - Anita B. Wandanaya (CCIT Journal, 2012)
Progress increasingly global information technology caused a change consumer behavior in buying products. Consumer demand services online marketing viathe Interneteasy, fast and can beaccessed from anywhere and anytime without being tied down at work globally. Basically, consumers always want the convenience if you want to buya product. All they wanted was an advertising information over the Internet canbe accessed from anywhere around the world and at anytime available at the time they need a product. Company, especially marketers realize that they currently can not depend on traditional marketing. To be able to increase sales volume then should marketer be able to implement an advertising program that is the internet with online marketing. By implementing this program is expected to help companies get more profit. The purpose of this paper is to determine whether advertising and marketing programs over the Internet can influence purchasing decisionsof internet user sin buying a product.